2009
DOI: 10.1007/978-3-642-04769-5_6
|View full text |Cite
|
Sign up to set email alerts
|

Test Collection-Based IR Evaluation Needs Extension toward Sessions – A Case of Extremely Short Queries

Abstract: Abstract. There is overwhelming evidence suggesting that the real users of IR systems often prefer using extremely short queries (one or two individual words) but they try out several queries if needed. Such behavior is fundamentally different from the process modeled in the traditional test collection-based IR evaluation based on using more verbose queries and only one query per topic. In the present paper, we propose an extension to the test collection-based evaluation. We will utilize sequences of short que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 16 publications
3
37
0
1
Order By: Relevance
“…While, for generated queries of length 3, the performance, in terms of MAP was 0.30, 0.1950 and 0.266, respectively. Also, on the whole the queries generated appeared quite sensible: and reflected the querying behavior observed in the study by Keskustalo et al [16], referred to as S3. S3 was the most common strategy they observed, and was where users would issue multiple queries of length three: pivoting on two key words, and then varying the third query term.…”
Section: Simulated Interactionsupporting
confidence: 67%
See 1 more Smart Citation
“…While, for generated queries of length 3, the performance, in terms of MAP was 0.30, 0.1950 and 0.266, respectively. Also, on the whole the queries generated appeared quite sensible: and reflected the querying behavior observed in the study by Keskustalo et al [16], referred to as S3. S3 was the most common strategy they observed, and was where users would issue multiple queries of length three: pivoting on two key words, and then varying the third query term.…”
Section: Simulated Interactionsupporting
confidence: 67%
“…For example, in practice users often issues short queries [22], but longer queries have been shown to be more effective [14]. Kestalous et al [16] tried to justify this strategy empirically, and showed that a series of extremely short queries can be quite effective for finding one highly relevant document. But searching for a number of relevant documents often requires numerous queries to be posed during the search session [15].…”
Section: Or Invoke Some Other Combination Of Interactions?mentioning
confidence: 99%
“…Query Generation Keskustalo et al [13] proposed a series of idealised, prototypical approaches to generating queries, as identified from a user study. In particular, strategy QS3 identified by the authors offered reasonably good performance.…”
Section: User Simulations Setupmentioning
confidence: 99%
“…7 Two pivot terms were selected, with an additional third term added. However, users have been shown to steadily build up their queries as they acquire more information, first issuing short queries then increasing their length [13]. To this end, we created a modified querying strategy, taking the pivot terms, issuing these as individual queries first, and then combining them as the pivot.…”
Section: User Simulations Setupmentioning
confidence: 99%
See 1 more Smart Citation